Cell-mediated and humoral immunity in West syndrome - Montelli, T. C. B.; Iwasso, M. T. R.; Peracoli, M. T. S.; Mota, N. G. S. (FapUNIFESP (SciELO), 1981)
The immunological status of five children with West syndrome consequent to previous cerebral lesions was investigated. Three children had West syndrome and two were in transition from West to Lennox-Gastaut syndrome. All of them showed cellular immunological deficiencies in the following tests: sensitization to DNCB, intracutaneous reaction to PHA, inhibition of leukocyte migration, blastic transformation of lymphocytes, T and B lymphocytes in peripheral blood and levels of serum immunoglobulins. These immunological deficiencies, of different degrees of severity, were associated with frequent infections in these children. A possible association between the immunological deficiencies and autoimmunity is discussed.
Keywords: 1 chloro 2,4 dinitrobenzene; clonazepam; corticotropin; nitrazepam; phenobarbital; phytohemagglutinin; b lymphocyte; brain injury; cellular immunity; central nervous system; drug therapy; electroencephalography; etiology; humoral immunity; immune deficiency; infant; lennox gastaut syndrome; major clinical study; pathogenesis; preschool child; t lymphocyte; therapy; west syndrome; Antibody Formation; Case Report; Child, Preschool; Female; Human; Immunity, Cellular; Immunoglobulins; Infant; Lymphocyte Activation; Male; Skin Tests; Spasms, Infantile; Syndrome